2014
DOI: 10.2190/na.35.4.d
|View full text |Cite
|
Sign up to set email alerts
|

Perishable Fiber Artifacts and Paleoindians: New Implications

Abstract: Recent research demonstrates that perishable industries-notably including the manufacture of textiles, basketry, cordage, netting, and sandals-were a well-established, integral component of the Upper Paleolithic technological milieu in many parts of the Old World. Moreover, extant data suggest that these technologies played a vital and, hitherto, utterly unappreciated role in the ecological success of late Pleistocene populations, including the first Americans. This article explores the varied roles of early f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 44 publications
0
5
0
4
Order By: Relevance
“…Later in the Holocene, references to finds of tools, wooden structures and plant fibres preserved on coasts and in lakes in northern Europe become increasingly numerous (Fischer 1995;Wigforss 2014). These data show that people developed the technique of plaiting or braiding and twining fibres, which had various applications on different continents and in various situations (Adovasio et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 91%
See 1 more Smart Citation
“…Later in the Holocene, references to finds of tools, wooden structures and plant fibres preserved on coasts and in lakes in northern Europe become increasingly numerous (Fischer 1995;Wigforss 2014). These data show that people developed the technique of plaiting or braiding and twining fibres, which had various applications on different continents and in various situations (Adovasio et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 91%
“…In the Americas, remains of cordage, basketry and textiles from Meadowcroft rockshelter, Paisley caves, Cueva del Guitarrero and Monte Verde etc. have been directly dated to between 12 and 10 ka bp (Adovasio et al 2014). In the Middle East, Linum usitatissimum (flax) microfibres were identified from Dzudzuana Georgia in cave levels dated to ca.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Our ensuing research identified 79 impressions of plant-based cordage and cordage constructions present at three sites: Dolni Vestonice I, II, and Pavlov I (Adovasio et al, 2001a(Adovasio et al, , 2001bSoffer and Adovasio, 2004;Soffer et al, 1998Soffer et al, , 2002. They included as a variety of twined and plain-woven textiles made on non-heddle looms or weaving frames.…”
Section: What We Discoveredmentioning
confidence: 99%
“…Despite general agreement of various lines of evidence, the evidence remains indirect. Preservation biases that favor projectile points and animal bone compared to plant materials could, to some extent, inflate the hunting signal [20][21][22]. The biases of previous researchers who have generally been males from a culture in which hunting is a distinctly masculine pursuit could furthermore inflate the hunting signal [23].…”
Section: Introductionmentioning
confidence: 99%